Konformitas Internalisasi Peserta Didik terhadap Peraturan Sekolah serta Implikasinya dalam Bimbingan dan Konseling - Rahmadinu, Wisda; Marjohan, Marjohan; Syahniar, Syahniar (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2022)
This research was initiated by the condition of students who still have no internalized conformity to school regulation. Basically, each learner has different awareness in conforming school regulation. Some of them do it because of their self-awareness, and othersdo it because of their anxiety to behave and obey school regulation. The objectives of this research were to describe (1) the internalized conformity of students to school regulation concerning the way they dress, (2) the internalized conformity of students to school regulation concerning the way they behave, (3) internalized conformity to school regulation in conforming, (4) and the difference of internalized conformity to school regulation between male and female students. This research used quantitative approach with descriptive comparative, with 251 students as sample chosen by using proportional random sampling tecnique. The result revealed that the level of internalized conformity of students to school regulation was in medium category. There was a difference of internalized conformity to school regulation between male and female students.